Malong: the magic cloth - Ordinario, Mary Ann (ABC Educational Development Center, 2016)
"What makes the Malong so special? Find out the mystery of the magic cloth as a little boy tells his true-to-life exceptional journey with his family. Children carry a little bit of enchantment all the time. This is the ultimate book for them to discover the magical things around them."--Back cover.